Literature Review: Effectiveness of Moringa Leaves (Moringa oleifera) to Diabetes Mellitus - Lucya Rahayu Putri; Elsa Yuniarti (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2023)
Moringa oleifera (Moringa leaves) is often used in herbal medicine. Many compounds in Moringa leaves such as flavonoids, vitamins, and alkaloids. This article was written with the aim of knowing the effectiveness of Moringa leaves against diabetes mellitus. The method used is a literature review combined with a search for related sources on Google Scholar for 2012 to 2022. The results of the literature review of the articles carried out can be concluded that the effectiveness of Moringa leaves has a significant effect on the insulin hormone. This is because Moringa leaves contain flavonoids, vitamins, and alkaloids which are rich in antioxidants. Antioxidants contained in Moringa plants can prevent lipid peroxidation by peroxy radicals. In conclusion, Moringa leaves can prevent diabetes mellitus.